Climate science must unlock solutions in new era - Mukherji, Aditi (2025)
As 1.5 degrees Celsius of warming is reached, climate science must look to the future, writes Aditi Mukherji, director of CGIAR’s Climate Change Adaptation and Mitigation Impact Action Platform and IPCC author.